Liquid Biopsy in Cancer Patients : The Hand Lens for Tumor Evolution - Russo, Antonio; Giordano, Antonio; Rolfo, Christian (Springer International Publishing : Imprint: Humana Press, 2017)
This text is designed to provide readers with a useful and comprehensive resource and state-of-the-art overview about the new, growing and fast-expanding field of "liquid biopsy" for the management of cancer patients. The liquid biopsy represents an important turning point in oncology since it provides a tool for a serial monitoring of disease. Liquid biopsy is our "hand lens" to follow molecular changes that characterize tumor development and progression. The book provide a unique and valuable resource on the clinical relevance of liquid biopsy as well as on the technical aspects of liquid biopsy analysis. All invited authors are recognized experts in their field. Liquid Biopsy in Cancer Patients: The Hand Lens for Tumor Evolution is targeted to resident and fellows physicians, medical oncologists, molecular biologists and biotechnologists.
Keywords: Medicine.; Oncology.; Pathology.; elektronické knihy; electronic books